The International Handbook on the Sociology of Education: An International Assessment of New Research and Theory - Torres, Carlos Alberto; Antikainen, Ari (Rowman & Littlefield Publishers, 2002)
The twentieth century has been marked by the expansion of educational opportunities worldwide. It has been the century of education, and the role of the state in the promotion of public education has been decisive. Yet, at the millennium's turn efforts to diminish the role of the state are rapidly changing education, especially in terms of its role in democracy. This comprehensive handbook offers a fresh view of the social context of education, outlining the challenges as well as the advances in public and private education systems. The book offers a systematic account of current social theory and methodologies, applied perspectives on the development of education in many regions of the world, and compares key themes such as access, school choice, equity, and educational performance.